Rubidium 2,4,6-trioxo-1,3-diazinan-5-ide–1,3-diazinane-2,4,6-trione–water (1/1/1) - Gryl, Marlena (International Union of Crystallography, 2011)
The asymmetric unit of the title compound, Rb(+)·C(4)H(3)N(2)O(3) (−)·C(4)H(4)N(2)O(3)·H(2)O, consists of one rubidium cation, a barbituric acid molecule, a barbiturate anion and one water molecule. The rubidium ion has seven close-contact interactions with O atoms, with Rb⋯O distances ranging from 2.8594 (16) to 3.2641 (14) Å. These seven O atoms together with an eighth O atom at 3.492 (2) Å away from Rb form a distorted polyhedron with shape intermediate between an antiprism and a dodecahedron. The Rb(+) ions connect layers built of organic components and water molecules linked via N—H⋯O and O—H⋯O hydrogen bonds.